Mothers' Reactions to Children's Emotion Expressions in Different Cultural Contexts: Comparisons across Nepal, Korea, and Germany. Issue 5 (4th July 2022) - Cho, Sook in; Song, Ju-Hyun; Trommsdorff, Gisela; Cole, Pamela M.; Niraula, Shanta; Park, Seong-Yeon
ABSTRACT: The current study examined (1) cross-cultural variations in mothers' reports of how they would react to their children's positive and negative emotions as triggered by different interpersonal situations and (2) their relations to children's emotion regulation competence in Nepal, Korea, and Germany. Participants were 305 mothers whose children were first graders in elementary school. Mothers reported their reactions to children's positive and negative emotions in hypothetical social scenarios and evaluated their children's emotion regulation using a standardized measure. Research Findings: German mothers reported higher levels of emotion encouragement, while Nepali mothers reported higher levels of punitive and distress reactions. Korean mothers reported higher levels of distress reactions. Mothers' encouragement of children's pride expression was associated differently with children's emotion regulation in each culture – negatively related in Nepal, unrelated in Korea, and positively related in Germany, whereas mothers' distress in response to children's shyness was related to children's poorer emotion regulation in all cultures. Practice or Policy: These findings highlight the importance of contexts – in terms of both culture and specific emotions children express – in interpreting the meanings of emotion socialization practices. This research suggests considering cultural influences in designing parenting interventions to promote children's emotional competence aligning with cultural expectations.